Anthropogenic 236U and Pu at remote sites of the South Pacific. (September 2019) - Froehlich, M.B.; Akber, A.; McNeil, S.D.; Tims, S.G.; Fifield, L.K.; Wallner, A.
Abstract: Anthropogenic radionuclides, like 236 U and 239, 240 Pu, are present in the environment as a result of global fallout from nuclear weapons tests conducted in the 1950s and 1960s and can potentially be used as tracers in soil erosion and sediment movement studies. Here, we report data on 236 U and 239, 240 Pu in soil samples from the Motueka Valley (New Zealand) and for the first time from two remote islands Rarotonga and Atiu (Cook Islands) in the South Pacific. 236 U and 239, 240 Pu were measured using Accelerator Mass Spectrometry (AMS) at the Australian National University. The 236 U and 239 Pu isotope concentrations versus soil depth and the 240 Pu/ 239 Pu and 236 U/ 239 Pu isotope ratios are discussed for each site. The radionuclide depth dependence revealed any soil disturbance, whereas the isotopic signatures indicated the source of the radionuclides' origin. Highlights: Exploration of uranium-236 ( 236 U) and plutonium-239 ( 239 Pu) in the Southern Hemisphere by Accelerator Mass Spectrometry. We report the depth profiles for both isotopes from three remote sites in the South Pacific. The weighted average 240 Pu/ 239 Pu and 236 U/ 239 Pu isotopic ratios indicate different origins across the three locations.